2015
DOI: 10.7554/elife.07811
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress contributes to the expression of the STM homeobox gene in Arabidopsis shoot meristems

Abstract: The role of mechanical signals in cell identity determination remains poorly explored in tissues. Furthermore, because mechanical stress is widespread, mechanical signals are difficult to uncouple from biochemical-based transduction pathways. Here we focus on the homeobox gene SHOOT MERISTEMLESS (STM), a master regulator and marker of meristematic identity in Arabidopsis. We found that STM expression is quantitatively correlated to curvature in the saddle-shaped boundary domain of the shoot apical meristem. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 86 publications
(141 reference statements)
8
129
0
Order By: Relevance
“…We recently showed that mechanical perturbations in the form of ablation in the SAM is sufficient to induce CUC3 expression in the SAM, while CUC1 expression profile remains largely unaffected in the same conditions. 26 Here we further confirm this result: No significant induction of signal or change in signal patterning was detected in the pCUC1:: CUC1-GFP line after ablation (Fig. 1C upper panels).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…We recently showed that mechanical perturbations in the form of ablation in the SAM is sufficient to induce CUC3 expression in the SAM, while CUC1 expression profile remains largely unaffected in the same conditions. 26 Here we further confirm this result: No significant induction of signal or change in signal patterning was detected in the pCUC1:: CUC1-GFP line after ablation (Fig. 1C upper panels).…”
supporting
confidence: 76%
“…4,15,32 A key question for the future is the analysis of the interplay between mechanical forces and the molecular regulators of meristem function (Fig. 1A).In a recent article, 26 we showed that a master regulator of meristem maintenance, the homeodomain protein SHOOT MERISTEMLESS (STM) is expressed at a higher level in the boundary domain, and that this local increase in promoter activity can be related to mechanical stress: mechanical perturbations are sufficient to induce STM expression in the meristem. Interestingly, mechanical perturbations do not affect all boundary-expressed genes in the same way.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stacks of 1,024 × 1,024 pixels of three dissected meristems, with Z slices every 0.5 μm, were acquired every 12 h during 48 h on a Zeiss LSM 700 upright confocal microscope, with a 40× water-dipping lens. Stacks from the kinetics were processed with a C++ script, using the Level Set method (45) to detect the surface of the meristem at high resolution. Meshes of these surfaces were then created with MorphoGraphX (17,46).…”
Section: A Mechanical Division Rule Provides Better Predictions For Dmentioning
confidence: 99%
“…Thus, the lock on organ identity probably resides in the final pattern of the meristematic tissues. It might be encoded in the tensile stress networks that characterize different cell arrangements as mechanical forces regulate key meristem factors including STM (Landrein et al, 2015). Alternatively, the size and shape of the lateral organ might alter the distribution of morphogens or the penetration of exogenous cytokinin, as well as other compounds, which control meristem functions.…”
Section: What Locks Organ Identity?mentioning
confidence: 99%